The Psychological Impact of Amblyopia Treatment: A Systematic Literature Review - Louisa Haine; Isaac Taylor; Megan Vaughan (British and Irish Orthoptic Journal)
Aim: The aim of this literature review was to determine if a consensus could be reached on whether amblyopia treatment causes distress to patients and/or their guardians, and if so, establish the impact of this reported psychological distress upon paediatric patients and/or their parents/guardians. Methods: A systematic review of the literature was conducted of all publications written in English. Search terms included both MeSH terms and alternatives related to amblyopia and psychological distress. Evidence quality was assessed using an adapted Newcastle-Ottawa Score (NOS) and evaluation of the literature was used to form a narrative synthesis of the findings. Results: Initial searches yielded 7,838 titles in total, with 25 peer reviewed papers published between 1999 and 2021 meeting the study inclusion criteria. Factors such as the presence of strabismus, moderate and severe amblyopic density, occlusive patch treatment and patching during school age increase the likelihood of experiencing distress as a result of amblyopia treatment. Conclusions: Both parents/guardians and patients can experience psychological distress as a result of undertaking amblyopia treatment. School-aged children and those receiving occlusion therapy in the form of patching report higher distress than infants and young-children, and those receiving atropine occlusion therapy or refractive correction only. Further study measuring the physiological markers of distress such as Cortisol and BDNF, is recommended.